2015
DOI: 10.1016/j.ajpath.2015.03.021
|View full text |Cite
|
Sign up to set email alerts
|

Expression of 15-Hydroxyprostaglandin Dehydrogenase in Human Chorion Is Associated with Peroxisome Proliferator-Activated Receptor Isoform Expression in Term Labor

Abstract: Chorionic NAD-dependent 15-hydroxy prostaglandin dehydrogenase (PGDH) plays a pivotal role in controlling the amount of prostaglandins in the uterus. Peroxisome proliferator-activated receptors (PPARs) are implicated to be involved in parturition. In this study, we investigated whether PPARs are involved in control of PGDH expression in chorion. The chorionic tissues were collected from the following groups of the women with singleton pregnancy: term no labor (TNL), term labor (TL) and preterm labor (PTL). Cho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Numerous studies indicated that placental intrauterine infection was strongly associated with sPTL or PPROM (Salafia et al, 1991;Helmig et al, 2002;Morgan, 2016;Pugni et al, 2016;Chisholm et al, 2018). A study in humans demonstrated that HPGD expression in preterm-labor placenta tissues was decreased in comparison with a full-term labor group (He et al, 2015). HPGD is a member of the short-chain non-metalloenzyme alcohol dehydrogenases protein family and is responsible for the degradation of prostaglandins, hormones that modulate the inflammatory response (Aoki and Narumiya, 2012;Seo and Oh, 2017).…”
Section: Proteins Involved In Infection and Inflammationmentioning
confidence: 99%
“…Numerous studies indicated that placental intrauterine infection was strongly associated with sPTL or PPROM (Salafia et al, 1991;Helmig et al, 2002;Morgan, 2016;Pugni et al, 2016;Chisholm et al, 2018). A study in humans demonstrated that HPGD expression in preterm-labor placenta tissues was decreased in comparison with a full-term labor group (He et al, 2015). HPGD is a member of the short-chain non-metalloenzyme alcohol dehydrogenases protein family and is responsible for the degradation of prostaglandins, hormones that modulate the inflammatory response (Aoki and Narumiya, 2012;Seo and Oh, 2017).…”
Section: Proteins Involved In Infection and Inflammationmentioning
confidence: 99%
“…29 Our previous studies have shown that corticotropinreleasing hormone and peroxisome proliferator-activated receptors play pivotal roles in the regulation of PGDH in the chorion during pregnancy. 23,30 Moreover, we have also demonstrated that reduced PGDH expression is associated AeC: The effect of NaHS on PGDH mRNA (A) and protein (B) expression as well as activity (C). Cells were treated with an increasing concentration of NaHS (10 À5 to 10 À4 mol/L) for 24 hours.…”
Section: Discussionmentioning
confidence: 86%
“…with decreased expression of peroxisome proliferatoractivated receptor-g and increased expression of glucocorticoid receptor and progesterone receptor A. 30,31 Herein, hydrogen sulfide produced locally increased PGDH expression in the chorion, and PGDH expression correlated with the expression level of hydrogen sulfideegenerating enzymes in the chorion. Taken together, this suggests that the PGDH expression level is controlled by a molecular network within the chorion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Natural ligands include all kinds of unsaturated fatty acids and their metabolic derivatives, such as linoleic acid, linolenic acid, and eicosapentaenoic acid. Certain prostaglandins and their metabolic derivatives also belong to natural ligands, and currently 15-deoxygenated prostaglandin is known to possess the strongest metabolic activity [ 12 ]. On the other hand, the synthetic ligand is mainly composed of thiazolidinedione compounds (troglitazone, rosiglitazone, pioglitazone, etc.).…”
Section: Overview Of Ppar γmentioning
confidence: 99%